2021
DOI: 10.1038/s41388-021-01891-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel homeostatic loop of sorcin drives paclitaxel-resistance and malignant progression via Smad4/ZEB1/miR-142-5p in human ovarian cancer

Abstract: The primary chemotherapy of ovarian cancer (OC) often acquires chemoresistance. Sorcin (SRI), a soluble resistance-related calcium-binding protein, has been reported to be an oncogenic protein in cancer. However, the molecular mechanisms of SRI regulation and the role and aberrant expression of SRI in chemoresistant OC remain unclear. Here, we identified SRI as a key driver of paclitaxel (PTX)-resistance and explored its regulatory mechanism. Using transcriptome profiles, qRT-PCR, proteomics, Western blot, imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…Our previous work revealed that SRI promoted the stemness and EMT process in ovarian cancer ( 35 ), we, therefore, wanted to investigate the association of SRI expression with stemness score and EMT-related genes in cancers. First, the sorcin expression was upregulated in the OVCAR-3 and SKOV-3 spheres cells compared with the respective adherent cells ( Supplementary Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous work revealed that SRI promoted the stemness and EMT process in ovarian cancer ( 35 ), we, therefore, wanted to investigate the association of SRI expression with stemness score and EMT-related genes in cancers. First, the sorcin expression was upregulated in the OVCAR-3 and SKOV-3 spheres cells compared with the respective adherent cells ( Supplementary Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Genomic amplification of SRI has long been recognized as an occasional event of such genomic co-amplification ( 52 ). However, accumulating evidence indicated that the pathways involved in the tumor malignant behaviors, such as TGF-β and JAK-STAT3 signaling were affected by the SRI gene amplification ( 35 , 53 ). In addition, we found co-occurrence of ADAM22, DBF4, ABCB1, ABCB4, and RUNDC3B alterations was observed with the SRI alterations, which was consistent with the previous reports ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, miR-142 promoted organoid formation by breast cancer stem cells (BCSCs) and enhanced tumor growth initiated by human BCSCs in vivo [ 14 ]. In ovarian cancer, miR-142-5p significantly decreased cell proliferation, arrested the cell cycle at the S phase, reduced the ability of colony formation, inhibited cell migration and invasion, and enhances cisplatin-induced apoptosis [ 15 , 16 ]. Zhang et al showed that low miR-142 expression was associated with a worse survival [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In ovarian cancer, miR-142-5p significantly decreased cell proliferation, arrested the cell cycle at the S phase, reduced the ability of colony formation, inhibited cell migration and invasion, and enhances cisplatin-induced apoptosis [ 15 , 16 ]. Zhang et al showed that low miR-142 expression was associated with a worse survival [ 15 ]. In contrast, our study revealed that low miR-142 expression seemed to be correlated with a better survival.…”
Section: Discussionmentioning
confidence: 99%